2020
DOI: 10.3389/fpsyg.2020.02002
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Physical Activity on Drug Cravings of Drug Addicts With AIDS: The Dual Mediating Effect of Internal Inhibition

Abstract: Background As a global infectious disease, Acquired Immune Deficiency Syndrome (AIDS) poses a serious threat to the safety and health of the society. In recent years, the proportion of drug addicts infected with HIV has been increased, and drug addicts became one of the main carriers of the spread of AIDS, which has attracted worldwide attention. It has been reported that physical activity has positive effects on improving the inhibitory function of drug addicts and reducing their drug craving, bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 54 publications
(47 reference statements)
0
4
0
Order By: Relevance
“…Zhang et al (2020) [ 23 ] point out exercise intensity and exercise frequency are divided into 1–5 cases, with 1–5 points, respectively, and exercise time is split into 1–5 types, with 0–4 points, respectively. According to the question options, in the aspect of exercise intensity, it is split into five intensities from A to E. In terms of exercise frequency, it is divided into five frequencies from A to E. In terms of time, it is also divided into five types from A to E according to the options.…”
Section: Basic Theory and Research Methodsmentioning
confidence: 99%
“…Zhang et al (2020) [ 23 ] point out exercise intensity and exercise frequency are divided into 1–5 cases, with 1–5 points, respectively, and exercise time is split into 1–5 types, with 0–4 points, respectively. According to the question options, in the aspect of exercise intensity, it is split into five intensities from A to E. In terms of exercise frequency, it is divided into five frequencies from A to E. In terms of time, it is also divided into five types from A to E according to the options.…”
Section: Basic Theory and Research Methodsmentioning
confidence: 99%
“…Recreation involves physical, emotional, and social activities that achieved through sports, play and travel. Based on the previous research conducted by Tingran Zhang, in 2020, it is also found that an environment-friendly rehabilitation method has exercises, and it has attracted attention as one of treatment for drug addiction [9], this becomes one of the reasons that gym was designed as one of facilities for the rehabilitants. The above activities require space as a facility to make rehabilitant gets a well treatment towards recovery and no longer addicted to drugs.…”
Section: Drug-addictive Rehabilitation Centermentioning
confidence: 99%
“…In recent years, there has been an increase in studies on physical activity and the risk of relapse (Motaghinejad et al, 2015;K. Wang et al, 2019;T. Zhang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Exercise training is a high-benefit low-risk intervention for most patients. In recent years, there has been an increase in studies on physical activity and the risk of relapse (Motaghinejad et al, 2015; K. Wang et al, 2019; T. Zhang et al, 2020). Exercise can also enable individuals with drug addiction to achieve better fitness results and improve their psychological states, such as positive changes in personality and psychological characteristics, including emotional improvement, self-confidence, and willpower.…”
Section: Introductionmentioning
confidence: 99%